Freshwater Mussel Bed Habitat in an Alluvial Sand-Bed-Material-Dominated Large River: A Core Flow Sediment Refugium? - Alan D. Christian; Andrew J. Peck; Ryan Allen; Raven Lawson; Waylon Edwards; Grace Marable; Sara Seagraves; John L. Harris (Diversity, 2020)
Habitat degradation, organismal needs, and other effects influencing freshwater mussel declines have been subject to intense focus by conservationists for the last thirty plus years. While researchers have studied the physical habitat requirements and needs of mussels in small- to medium-sized rivers with variable levels of success, less research has been conducted on mussel habitat in larger non-wadeable rivers, especially at the reach scale, where core flow environmental conditions provide and maintain habitat for freshwater mussels. We designed a quasi-experimental observational field study to examine seven hydrologic energy and material variables laterally and longitudinally at Current and Extirpated mussel bed habitat reaches in lower White River, Arkansas, a large non-wadeable, sand-bed-material-dominated river. As expected, lateral and longitudinal hydrologic variable differences were identified within a reach. Mean velocity, bed velocity, the Froude number, and stream power were all significantly lower at Current mussel bed habitat stations within a sampling reach. Energy regime differences in shear stress and, marginally, stream power were higher at Extirpated mussel bed habitat reaches. Several factors emerged as important to mussel habitat in the White River. First, bed velocity warrants further exploration in terms of both flow strength and flow direction. Second, bedload appears to be the primary contributor to mussel habitat but requires additional exploration within the context of core and secondary flow pathway interactions. The combined empirical evidence from our study supports the flow refugium concept identified for mussel habitats in smaller systems but expands the concept to large non-wadeable streams and includes reach-scale refuge from sediment transport conditions.